CORPORATE GOVERNANCE AND ACCOUNTABILITY: LEGAL MECHANISMS FOR PREVENTING BUSINESS MALPRACTICES - Harly Clifford Jonas Salmon (Penelitian dan Pengembangan Ilmu, 2025)
Effective corporate governance (CG) is the key to preventing business malpractice, such as fraud and corruption, which continues to be a global challenge. This research aims to explore the effectiveness of legal mechanisms in increasing corporate accountability and preventing business malpractice. This study focuses on identifying and evaluating various legal instruments that support CG implementation in various jurisdictions, as well as their impact on preventing business malpractice. This research uses a Systematic Literature Review (SLR) approach to collect and analyze 27 relevant articles from the Scopus, Web of Science and Springer databases. The literature selection process follows the PRISMA flow, which includes the stages of identification, screening and article eligibility. The research results show that legal instruments, such as government regulations, anti-fraud policies, and external monitoring systems, play a significant role in increasing corporate accountability. In addition, the implementation of law-based CG is effective in creating transparency, strengthening stakeholder protection, and preventing fraud and corruption. This study also found variations in legal instruments between countries, which were adapted to their respective social, political and economic conditions. This study confirms that the effectiveness of corporate governance is greatly influenced by the existence and implementation of strong legal mechanisms. Therefore, collaboration between the government, regulators and companies is needed to strengthen the legal system to support corporate governance that is accountable and free from business malpractice.